Application of NCRP 156 Wound Models for the Analysis of Bioassay Data from Plutonium Wound Cases. Issue 3 (September 2017) - Poudel, Deepesh; Guilmette, Raymond A.; Klumpp, John A.; Bertelli, Luiz; Waters, Tom L.
Abstract : Abstract: The NCRP 156 wound model was heavily based on data from animal experiments. The authors of the report acknowledged this limitation and encouraged validation of the models using data from human wound exposures. The objective of this paper was to apply the NCRP 156 wound models to the bioassay data from four plutonium-contaminated wound cases reported in the literature. Because a wide variety of forms of plutonium can be expected at a nuclear facility, a combination of the wound models—rather than a single model—was used to successfully explain both the urinary excretion data and wound retention data in three cases. The data for the fourth case could not be explained by any combination of the default wound models. While this may possibly be attributed to the existence of a category of plutonium whose solubility and chemistry are different than those described by the NCRP 156 default categories, the differences may also be the result of differences in systemic biokinetics. The concept of using a combination of biokinetic models may be extended to inhalation exposures as well, where more than one form of radionuclide—particles of different solubility or different sizes—may exist in a workplace.